Forecasting Tourist Visitor by System Dynamics Analysis A Case Study in Iran - Don Pan, Bing (International journal of industrial engineering and operational research, 2023)
This paper presents a comprehensive study on the forecasting of tourist visitors using System Dynamics analysis. The aim of this research is to develop a robust and accurate model that can effectively predict tourist arrivals in a given destination. The study employs a systematic approach, starting with an introduction to the importance of tourism forecasting, followed by a literature review of existing forecasting methodologies. Subsequently, the methodology section details the application of System Dynamics for tourist visitor forecasting. The paper then presents the numerical results obtained from the analysis, followed by a conclusion summarizing the findings and highlighting the significance of the proposed forecasting model. The paper concludes with a comprehensive list of references for further exploration and research in the field of tourism forecasting